Spiritual Formation and Mystical Symbolism - Zinn, Grover A.; Coulter, Dale M.; van Liere, Frans (Brepols, 2022)
Biblical interpretation, writings on the contemplative/mystical life and a continuing deep reflection on the nature and meaning of symbols come together in powerful ways in Victorine writers, particularly Hugh and Richard, as well as the lesser-known writer Thomas Gallus (Thomas of Vercelli), a Victorine canon who became the abbot of a house of regular canons in Vercelli, Italy. This volume contains: (1) Hugh’s <span class=